Investigating Amorphous Metal Composite Architectures as Spacecraft Shielding1. Issue 1 (11th December 2012) - Davidson, Marc; Roberts, Scott; Castro, Gerhard; Dillon, Robert Peter; Kunz, Allison; Kozachkov, Henry; Demetriou, Marios D.; Johnson, William L.; Nutt, Steve; Hofmann, Douglas C.
Abstract The threat of micro‐meteoroid and orbital debris (MMOD) collisions with spacecraft and satellites has been increasing with the increasing worldwide use of low earth orbit. Providing low‐areal‐density shielding for the mitigation of these high velocity impacts is essential for ensuring successful and cost effective missions. Here, we report results obtained from hypervelocity impact testing on bulk metallic glass (BMG) matrix composites. Their carbide‐like hardness, low melting temperatures, ultra‐high strength‐to‐weight ratio and the ability to be processed like polymers are material attributes ideally suited for spacecraft shielding, particularly as an outer wall bumper shield.